INFLUENCE OF THE VIEWERS ON THE PERFORMANCE RESULTS OF SPORTS TEAMS - Yushkin, V.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was a theoretical substantiation and description of the calculation of the rating using numerical methods in team sports. Methods and structure of the study. The formation of rating classifications in team sports was carried out using mathematical modeling using high-level programming languages ​​and numerical calculation methods. The requirements that must be met by the general targets, guidelines that form the rating of teams are determined: taking into account the results of previous performances, the factor of influence of one's field, the number of spectators at the stadium, the potential of teams. The mathematical model was evaluated by the indicator of the convergence of the current rating of the teams participating in the match with the actual result of the game. The analysis of the results of the performance of teams in the matches of the championships of Russia in 1992-2022 was carried out. Results and conclusions. Three variants of calculation were performed: 1) calculation of a unified system of equations, taking into account the factor of influence of one's own field; 2) calculation with the calculation of the index of the coefficient of influence of spectators on the results of games; 3) calculation of the coefficients of influence of the home field factor and spectators on the results of the games. The system of linear equations has a unique solution if the results of the teams' performance do not have zero uncertainty during the entire period of the competition. The developed rating system is aimed at numerical confirmation of the level of readiness and potential of teams, the accuracy of predicting the performance of teams in the short and long term in all team sports.